DEVELOPMENT OF HEURSTIC ABILITY - Khojayeva, G.A. (Educational Research in Universal Sciences, 2023)
The article provides information about communication skills, qualities that programmers should have, participation in projects with instructions for creating independent software projects, and skills required for professionals.